Sounding Dublin: Mapping Popular Music Experience in the City - O'Flynn, John; Mangaoang, Áine (Journal of World Popular Music, 2019)
This article interrogates ideas of popular music "sound(s)" linked to place by interpreting data gathered during the applied research project Mapping Popular Music in Dublin (MPMiD) 2015-16. An outline background, rationale and framework for MPMiD is presented, followed by a review of methods developed and overall themes that emerged. Focusing on the project’s "Sounding Dublin" strand, the article analyses the responses of 366 participants from a section of MPMiD’s e-survey relating to music, musicians, sounds and soundtracks that might be considered "typical" (or otherwise) of Dublin. Although a substantial minority of participants eschew notions of sonic uniqueness linked to place in the abstract sense, the data reveal a rich tapestry of experiences and standpoints linked to ideas of a Dublin sound or sounds. Some appear to concur with conventional hagiographies of rock and folk, with others challenging received narratives and proposing alternative viewpoints, scenes and pathways. "Dublin-specific" associations emerging across various genres are based on appraisals of performer engagement, accent and timbre, and narrative/lyrical style.